Carbon Storage Estimation in Mangrove Sediment at Payung Island, South Sumatera - Septi Hermialingga; Rujito Agus Suwignyo; Tengku Zia Ulqodry (Program Pascasarjana Universitas Sriwijaya, 2020)
Mangrove is a plant generally located in tropical regions. It grows in areas with salinated to fresh water and affected by tidal along with anaerobic soil conditions, where many grow in areas that are filled with mud and contain organic material. In the process of photosynthesis, mangrove captures carbon in the atmosphere and are stored in biomass and sediment. Sediment can store carbon greater than biomass and is rich of organic matter. Research regarding carbon storage in mangrove sediment on Payung Island has never been carried out which made this research aimed to estimate carbon storage in mangrove sediment on Payung Island. This research was conducted in October 2020 on Payung Island, South Sumatra and sediment samples were analyzed by the Walkley-Black oxidation method and the sediment texture was analyzed by the Shepard triangle method. The calculation results show the dominant sediment texture was in the clay category, the average value at each station for % C organic is 5,04% and % organic matter is 8,18% and carbon deposits in sediment are 129,6 tonC/ha.